Leader purposefulness within servant leadership: Examining the effect of servant leadership, leader follower-focus, leader goal-orientation, and leader purposefulness in a large u.s. healthcare organization - Justin A. Irving; Julie Berndt (Administrative Sciences, 2017)
As the study of servant leadership expands beyond theoretical exploration, empirical research continues to validate the positive effect of servant leadership behaviors and attitudes on diverse follower and organizational measures. This study expands the conversation by engaging the theme of leader purposefulness within servant leadership studies. A sample of over 1700 employees from a large U.S. healthcare organization provided responses to five research instruments. Follower perspectives on servant leadership, leader follower-focus, leader goal-orientation, and leader purposefulness were assessed using the Purpose in Leadership Inventory and each of these independent variables were analyzed for hypothesized positive relationships with four dependent variables: follower job satisfaction, follower organizational commitment, follower person-organization fit, and follower perception of leadership effectiveness. Each of the 16 hypothesized relationships were supported at a statistically significant level (<0.001) with positive correlations ranging from 0.40 to 0.88. Regression analyses were conducted to provide predictive modeling and indicators of the relative importance of each independent variable on the related dependent variables.
Keywords: 350; servant leadership; leader purposefulness; leadership measurement; job satisfaction; organizational commitment; person organization fit; goal orientation; follower focus; meaning; spiritual leadership